INOVASI PELAYANAN PT POS INDONESIA CABANG WATAMPONE DI ERA E-COMMERCE DALAM MENINGKATKAN KUALITAS PELAYANAN YANG BERDAYA SAING - Sari, Rika; Idrus, Muhammad; Syam, Akbar (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2024)
This research aims 1) To determine the service quality of PT Pos Indonesia Watampone Branch, 2) To determine the innovations carried out by PT Pos Indonesia Watampone Branch in improving the quality of competitive delivery services. This research is qualitative research, namely research that intends to understand the phenomena experienced by research subjects, for example behavior, perception, motivation, action, existence, etc. The subjects in this research were at the PT Pos Indonesia Watampone Branch Office located on Jalan M.H. Thamrin, Bone Regency. This research uses qualitative data analysis techniques, following the concept given by Miles and Huberman, namely an activity that includes data reduction, data display, and conclusion drawing/ferification. The results of this research show that: 1) The forms of innovation implemented at the Watampone Branch Post Office include process innovation and product innovation. These include: O-ranger, M-pospay and Pos Order Number. These innovations are related to the type of organizational innovation, namely new methods of managing, coordinating and taking responsibility as well as business innovation. This innovation has superior advantages and added value to the process and management level benefits which are expected to improve the quality of competitive delivery services. However, this innovation is still not optimal due to limitations in human resources and promotion. 2) Service quality is measured using public service standards KEPMENPAN No.63/Kep/M.PAN/7/2003 which consists of six indicators, namely service procedures, completion time, service costs, service products, facilities and infrastructure and the competence of service providers Those at the Watampone Branch Post Office can be categorized as satisfactory, so they need to be maintained and those that are still not good need to be evaluated and improved.